Ahmad Zewail - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Muhammad Najib, Muhammad Nor (Penerbit UMP, 2011)
Ahmed Hassan Zewa il is an Egyptian-American scientist, and the winner of the 1"999 Nobel Prize in Chemistry for his work on femtochemist ry. He is the Linus Pauling Chair Professor Chemistry, Professor of Physics, and the Director of the Physical Biology Center for Ultrafast Science and Technology (UST) and the NSF Laboratory for Molecular Sciences (LMS) at the Californ ia Institute of Technology. His current research is devoted to dynamical chemistry and biology, with a focus on the physics of elementary processes in complex systems. A major research frontier is the new development of "4D ultrafast diffraction and microscopy'; making possible the imaging of transient . structures in space and time with atomic-scale resolution.